2015
DOI: 10.1021/acscatal.5b00765
|View full text |Cite
|
Sign up to set email alerts
|

Different Product Distributions and Mechanistic Aspects of the Hydrodeoxygenation of m-Cresol over Platinum and Ruthenium Catalysts

Abstract: Experimental measurements of the conversion of m-cresol over Pt and Ru/SiO 2 catalysts show very different product distributions, even when the reaction is conducted at similarly low conversions and the same operating conditions (300 °C, 1 atm). That is, although ring hydrogenation to 3methylcyclohexanone is dominant over Pt, deoxygenation to toluene and C−C cleavage to C 1 −C 5 hydrocarbons prevail over Ru. For understanding the differences in reaction mechanisms responsible for this contrasting behavior, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
160
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(185 citation statements)
references
References 49 publications
25
160
0
Order By: Relevance
“…The results obtained in the present work revealed that the reaction pathway for HDO of phenol strongly depends on the type of metal. Similar results have been reported in the literature for HDO of different model molecules ,,,…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results obtained in the present work revealed that the reaction pathway for HDO of phenol strongly depends on the type of metal. Similar results have been reported in the literature for HDO of different model molecules ,,,…”
Section: Introductionsupporting
confidence: 92%
“…The results of DRIFTS are cast in terms of two mechanisms, as supported by prior DFT and experimental investigations: (1) direct dehydroxylation of phenol to a partially unsaturated hydrocarbon surface species (e.g., C 6 H 5 *), with subsequent hydrogenation to benzene (by analogy with Ref. ), which is favored by metal surfaces such as Ru(0 0 0 1) or (2) a mechanism involving a keto tautomer intermediate, which may undergo selective hydrogenation of the carbonyl to 2,4‐cyclohexadienone (depending on the support), followed by dehydration to benzene. This was suggested to occur on Pd/ZrO 2 catalysts by experimental observations, as well as on Pt(1 1 1) …”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The selectivity towards 3‐methylcyclohexanone was 64.9 %, with the selectivities towards the other products being 27.3 % for toluene and 7.7 % for 3‐methylcyclohexanol. Toluene was also a major product when using a Ru/SiO 2 catalyst with a selectivity of 38.5 % . However, Ru/SiO 2 also catalyzed the cleavage of C−C bonds, yielding methane as another major product (43.4 % selectivity).…”
Section: Vapor‐phase Deoxygenation Over Novel Catalystsmentioning
confidence: 99%
“…Tan and co‐workers have compared the reaction pathways of Ru/SiO 2 and Pt/SiO 2 at 300 °C and atmospheric pressure of H 2 . Deoxygenation to toluene and C−C cleavage to C 1 –C 5 hydrocarbons prevail over Ru, whereas ring hydrogenation to form 3‐methylcyclohexanone is dominant over Pt . The catalytic activity of Ni, Pd, and Pt for the HDO of m ‐cresol over silica‐supported catalysts at 250 °C and atmospheric H 2 pressure has been investigated by Chen and co‐workers .…”
Section: Upgrading Lignin Pyrolysis Vapors By Hydrodeoxygenationmentioning
confidence: 99%